Photothermal and silver ion synergistic antibacterial hydrogel dressing and preparation method and application thereof

By adding silver nitrate solution to THB@mSF and AHA solutions, a hydrogel dressing with photothermal antibacterial synergistic silver ions is formed, which solves the problem of AgNPs being prone to clumping and sudden release of silver ions, achieving efficient and safe antibacterial effects and excellent photothermal properties, and is suitable for burn skin treatment.

CN116077719BActive Publication Date: 2025-03-18XI AN JIAOTONG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310083233.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-08
Publication Date
2025-03-18
Estimated Expiration
2043-02-08

AI Technical Summary

Technical Problem

In the prior art, while hydrogel dressings impart antibacterial properties, AgNPs are prone to clumping, and the sudden release of silver ions or AgNPs in the hydrogel can cause cytotoxicity.

Method used

By adding silver nitrate solution to a 2.3.4-trihydroxybenzaldehyde-coated silk microfiber (THB@mSF) dispersion and a amino-modified hyaluronic acid (AHA) solution, a hydrogel dressing with photothermal antibacterial synergistic silver ion antibacterial was formed.

Benefits of technology

This method avoids the agglomeration of AgNPs and prepares hydrogels loaded with AgNPs by reducing silver ions in situ, reducing the sudden release of silver ions, improving antibacterial properties and safety, and also has excellent photothermal properties, suitable for burn skin treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116077719B_ABST
    Figure CN116077719B_ABST
Patent Text Reader

Abstract

The invention discloses a photothermal and silver ion synergistic antibacterial hydrogel dressing and its preparation method and application, in which the pyrogallol group (2.3.4-trihydroxybenzaldehyde) in the hydrogel can reduce silver ions to AgNPs in situ, without introducing other reducing agents, avoiding the sudden release of silver ions, and at the same time, the pyrogallol group can react with the amino group (AHA) in the hyaluronic acid modified by hydrazide to produce a Schiff base reaction, providing certain adhesion and photothermal performance. The hydrogel has good antibacterial properties, and at the same time, a photothermal agent is used to carry out photothermal antibacterial to cooperate with silver ion antibacterial, realize dual antibacterial effects, and at the same time, the infection problem of Pseudomonas aeruginosa in the burn wound is dealt with, and then the healing of the burn wound is promoted, and the hydrogel dressing with photothermal antibacterial and silver ion antibacterial also has good adhesion and antioxidant capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of biomedical materials, and specifically relates to a photothermal and silver ion synergistic antibacterial hydrogel dressing and a preparation method and application thereof. Background Art

[0002] Despite great progress in fire safety and prevention, burns remain a pressing issue in global public health. Partial and full-thickness burns damage the epidermis and dermis of the skin and may reach its inner subcutaneous tissue. Burn wounds face serious problems of infection. Hydrogels are considered to be a promising wound dressing material due to their many advantages for burn wounds, including the ability to provide a beneficial moist environment for burn wounds and absorb excess wound exudate. In addition, they can also serve as a physical barrier to block bacteria and prevent wound infection, and can provide a certain role in wound repair.

[0003] Infections caused by Staphylococcus and Pseudomonas aeruginosa can significantly disrupt the process of burn wound repair, resulting in functional and structural damage to wound tissue. Antimicrobial wound dressings can address this problem by minimizing bacterial colonization and providing appropriate coverage of the injured area to aid epithelial regeneration. Therefore, hydrogels are loaded with antimicrobial agents to impart antimicrobial properties to address the above issues.

[0004] On this basis, silver-based antimicrobial agents with a broad antimicrobial spectrum are widely used in burn wound treatment. However, the antibacterial activity is affected by the particle size, and the pre-prepared AgNPs are prone to agglomeration, which affects the antibacterial activity. In addition, the sudden release of silver ions or AgNPs in hydrogels can cause cytotoxicity. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a hydrogel dressing with synergistic antibacterial properties of photothermal and silver ions and a preparation method and application thereof, so as to solve the problems in the prior art that while giving the hydrogel antibacterial properties, AgNPs are easy to agglomerate, and the sudden release of silver ions or AgNPs in the hydrogel can cause cytotoxicity.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] The preparation method of the photothermal and silver ion synergistic antibacterial hydrogel dressing comprises the following steps:

[0008] After the THB@mSF dispersion and the AHA solution were mixed in a volume ratio of (100-300):600, a silver nitrate solution was added, and the silver ions in the silver nitrate solution became silver nanoparticles to obtain a hydrogel dressing;

[0009] The preparation process of the THB@mSF dispersion is as follows: adding silkworm cocoon fragments into a sodium carbonate solution, boiling to obtain silk fibroin, shearing the silk fibroin with a strong alkaline solution to obtain silk fibroin fibers, mixing the silk fibroin fibers with 2.3.4-trihydroxybenzaldehyde, and reacting in an alkaline solution to obtain a THB@mSF dispersion;

[0010] The preparation process of the AHA solution is as follows: adding adipic acid dihydrazide, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 1-hydroxybenzotriazole to a hyaluronic acid solution, stirring evenly and adjusting the pH value to obtain a mixed solution, dialyzing the mixed solution, adding ethanol to the dialyzed mixed solution to obtain a precipitate, dialyzing and freeze-drying the precipitate to obtain AHA, and dissolving AHA in water to obtain an AHA solution;

[0011] The silver nitrate solution is a mixture of silver nitrate and water.

[0012] A further improvement of the present invention is:

[0013] Preferably, the concentration of the silver nitrate solution is 1.32-3.96 mg / mL; the concentration of the THB@mSF dispersion is 24 mg / mL, and the concentration of the AHA solution is 20 mg / mL.

[0014] Preferably, during the preparation of the THB@mSF dispersion, the mass concentration of the sodium carbonate solution is 0.50%; the boiled silk fibroin is washed and dried, and the silk fibroin is sheared by a strong alkaline solution;

[0015] The shearing process is: shearing the silk fibroin with 17.5M sodium hydroxide particles, washing the sheared silk fibroin with water and performing centrifugal treatment to obtain the sheared silk fibroin.

[0016] Preferably, in the process of preparing the THB@mSF dispersion, silk fibroin and 2.3.4-trihydroxybenzaldehyde are mixed in a molar ratio of 1:1, and reacted in an alkaline solution with a pH value of 11 at 60° C. to obtain a THB@mSF dispersion.

[0017] Preferably, during the preparation of the AHA solution, the concentration of the hyaluronic acid solution is 20 mg / mL, the molar ratio of adipic acid dihydrazide to hyaluronic acid is 30:1; the molar ratio of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to 1-hydroxybenzotriazole is 1:1; and the mixing ratio of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to hyaluronic acid is 5 mol:1 g.

[0018] Preferably, the pH of the AHA solution is adjusted to 6.8 during preparation, and the reaction is carried out for 12 hours after the pH is adjusted to be stable for 4 hours.

[0019] A photothermal and silver ion synergistic antibacterial hydrogel dressing prepared by any one of the preparation methods described above, wherein the main structure of the hydrogel dressing is a hydrogel network, in which silver nanoparticles are dispersed; in the hydrogel network, the phenolic hydroxyl group of THB, the aldehyde group of THB and the amino group of AHA are connected, the phenolic hydroxyl group of THB is connected to the phenolic hydroxyl group in THB, the silver nanoparticles are connected to AHA, and the silver nanoparticles are connected to THB.

[0020] An application of the above-mentioned photothermal and silver ion synergistic antibacterial hydrogel dressing, wherein the hydrogel dressing is used as a photothermal agent under 808nm near-infrared laser irradiation.

[0021] An application of the above-mentioned photothermal and silver ion synergistic antibacterial hydrogel dressing, wherein the hydrogel dressing is used to inhibit methicillin-resistant Staphylococcus aureus and Pseudomonas aeruginosa.

[0022] An application of the above-mentioned photothermal and silver ion synergistic antibacterial hydrogel dressing, wherein the hydrogel dressing is used for antibacterial, burn, wound surface and full-thickness wound repair.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The present invention discloses a method for preparing a hydrogel dressing with photothermal and silver ion synergistic antibacterial properties. The preparation method adds a silver nitrate solution to a 2.3.4-trihydroxybenzaldehyde-coated silk microfiber (THB@mSF) dispersion and an amino-modified hyaluronic acid (AHA) solution, and forms a hydrogel dressing with photothermal antibacterial properties and synergistic silver ion antibacterial properties through Schiff base and ion coordination. In the method, the pyrogallol group (2.3.4-trihydroxybenzaldehyde) can react with the amino group (AHA) at the tissue interface in the presence of an oxidant to provide a certain adhesion force. The pyrogallol group can also effectively remove free radicals at the wound to avoid excessive oxidative stress reactions. Then, the silver ions are reduced in situ in the hydrogel to prepare a hydrogel loaded with AgNPs, and the phenolic hydroxyl group can effectively reduce Ag in an alkaline environment. + Therefore, the 2,3,4-trihydroxybenzaldehyde (THB) used will induce Ag without introducing other reducing agents. + Reduction to AgNPs is simple and safe without the introduction of other reducing agents, avoiding the sudden release of silver ions and being oxidized. The raw materials of the preparation method have excellent biocompatibility, and the THB reducing agent used to synthesize AgNPs is simple and safe without the introduction of other reducing agents. At the same time, silver nitrate provides the role of a crosslinking agent. The hydrogel dressing prepared by this method has excellent photothermal properties, photothermal antibacterial synergistic silver ion antibacterial properties, and can be well applied in the field of burn skin treatment.

[0025] Furthermore, the silver nanoparticles (AgNPs) in the preparation method of the present invention have a relatively large specific surface area relative to silver in ionic form, thereby greatly increasing the probability of AgNPs contacting the surface of microorganisms. The synthesis of commonly used AgNPs is usually toxic and the preparation process is relatively complicated. The present invention synthesizes AgNPs through a simple and safe reducing agent. 2.3.4-Trihydroxybenzaldehyde (THB) may self-polymerize and coat the surface of mSF (THB@mSF) under oxidizing agent and alkaline conditions, thereby giving THB@mSF a certain photothermal effect. THB will induce Ag without introducing other reducing agents. + Reduced to AgNPs. In addition, AgNPs are used as photothermal agents due to their unique optical and electronic properties.

[0026] The present invention also discloses a photothermal and silver ion synergistic antibacterial hydrogel dressing, wherein the addition of mSF to the hydrogel dressing enhances the mechanical properties of the hydrogel; secondly, it imparts certain photothermal properties, and the temperature rises by 26.2°C under 5 minutes of near-infrared laser irradiation; the AHA introduced into the hydrogel dressing network, firstly, the large number of carboxyl and hydroxyl groups available in the hyaluronic acid structure make it highly hydrophilic, and this property allows hyaluronic acid to absorb exudates. In addition, the biodegradability, biocompatibility and simple chemical modification of hyaluronic acid promote its application in wound healing, aiming to regulate inflammation and promote the re-epithelialization process. The hyaluronic acid macromolecule is modified with adipic acid dihydrazide groups as a hydrogel skeleton material to provide a certain number of amino groups. Finally, the amino hyaluronic acid can react with 2.3.4-trihydroxybenzaldehyde having a catechol group to produce a stable cross-linked network. The silver nitrate solution used first provides excellent antibacterial properties; secondly, the reduced AgNPs are used as photothermal agents due to their unique optical and electronic properties; then, silver ions play the role of crosslinkers by forming silver ion-carboxyl coordination complexes with the carboxyl groups of mSF and AHA. Silver ions first interfere with the synthesis of cell walls, causing the cell walls to lose their integrity and lose their protective effect against osmotic pressure, thereby damaging the bacteria and achieving a bactericidal effect. The hydrogel has good antibacterial properties, and uses photosensitizers for photothermal antibacterial to cooperate with silver ion antibacterial to achieve dual antibacterial effects. At the same time, it addresses the infection problem of Pseudomonas aeruginosa on burn wounds, thereby promoting the healing of burn wounds. The hydrogel dressing with photothermal antibacterial and silver ion antibacterial also has good adhesion and antioxidant capacity.

[0027] The present invention also discloses the application of a hydrogel dressing with synergistic antibacterial effects of photothermal and silver ions. The hydrogel can be used as a photothermal agent. Near-infrared light irradiates the photothermal agent to convert light energy into heat for antibacterial treatment. This application method is less invasive and has strong tissue penetration. At the same time, the laser is only focused on the target area, and has less impact on the whole body. Therefore, the synergistic antibacterial effect of antibacterial agents and near-infrared lasers may be a more promising strategy for preventing bacterial infection of burn wounds.

[0028] The present invention also discloses the application of a hydrogel dressing with synergistic antibacterial effects of photothermal and silver ions. The hydrogel can damage the cell membrane, and the ions can damage the cell membrane, which is an important component of bacterial life activities. If the cell membrane is damaged, the bacteria will die.

[0029] The present invention also discloses the application of a hydrogel dressing with photothermal and silver ion synergistic antibacterial properties. The hydrogel has dual antibacterial properties of photothermal antibacterial and silver ion antibacterial properties. It not only uses photothermal properties to produce obvious photothermal antibacterial effects on Pseudomonas aeruginosa and methicillin-resistant Staphylococcus aureus, but also uses the antibacterial properties of silver ions themselves to produce good antibacterial properties on the above two bacteria. It is helpful to inhibit bacteria on burn wounds and promote the healing of burn wounds. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] FIG. 1( a ) is a scanning electron microscope image of mSF prepared in the present invention; FIG. 1( b ) is a scanning electron microscope image of THB@mSF.

[0031] Figure 2 is an X-ray photoelectron spectroscopy (XPS) diagram of mSF and THB@mSF prepared in the present invention, wherein 2(a) is a general diagram; 2(b) is a C1s spectrum diagram of mSF; and 2(c) is a C1s spectrum diagram of THB@mSF.

[0032] FIG3( a ) is a photothermal image of mSF and THB@mSF prepared in the present invention; FIG3( b ) is a cyclic photothermal image of THB@mSF.

[0033] Figure 4 shows the scanning electron microscope images and energy spectrum of four hydrogels AHA / THB@mSF / Ag0, AHA / THB@mSF / Ag1, AHA / THB@mSF / Ag2, and AHA / THB@mSF / Ag3 prepared by the preparation method of the present invention. Among them, Figure 4(a) is the scanning electron microscope image of the four hydrogel dressings; Figure 4(b) is the energy spectrum of the AHA / THB@mSF / Ag0 hydrogel dressing; Figure 4(c) is the energy spectrum of the AHA / THB@mSF / Ag2 hydrogel dressing.

[0034] Figure 5(a) is a strain scan of the AHA / THB@mSF / Ag2 hydrogel dressing prepared in the present invention; Figure 5(b) is the rheological behavior of the AHA / THB@mSF / Ag2 hydrogel dressing with alternating strain switching from 1% to 500% for three cycles.

[0035] Figure 6 This is a graph showing the adhesion strength of the hydrogel dressing to pig skin.

[0036] FIG. 7( a ) is a swelling diagram of the AHA / THB@mSF / Ag hydrogel dressing prepared in the present invention; FIG. 7( b ) is a DPPH free radical scavenging rate diagram of the hydrogel dressing.

[0037] FIG8 is a photothermal image of the AHA / THB@mSF / Ag hydrogel dressing prepared by the present invention. FIG8 is a photothermal image of the AHA / THB@mSF / Ag hydrogel dressing prepared by the present invention. 2 Temperature change curves of hydrogel dressings under different photothermal intensities; Figure (b) is the infrared thermal image of the hydrogel dressing under 808nm irradiation.

[0038] Figure 9 (a) is a graph showing the results of the cell activity test of mouse fibroblasts (L929) using the AHA / THB@mSF / Ag hydrogel dressing contact method prepared by the present invention; (b) is a live / dead staining graph of L929 cells after contact with the AHA / THB@mSF / Ag hydrogel dressing prepared by the present invention for 24 hours.

[0039] FIG10 is an antibacterial graph of the AHA / THB@mSF / Ag hydrogel dressing prepared in the present invention. Among them, (a) is the antibacterial result diagram of the AHA / THB@mSF / Ag hydrogel dressing prepared by the present invention after contacting with Pseudomonas aeruginosa and methicillin-resistant Staphylococcus aureus; (b) is the antibacterial result diagram of the AHA / THB@mSF / Ag2 hydrogel dressing prepared by the present invention against Pseudomonas aeruginosa under near-infrared laser irradiation; (c) is the antibacterial result diagram of the AHA / THB@mSF / Ag2 hydrogel dressing prepared by the present invention against methicillin-resistant Staphylococcus aureus under near-infrared laser irradiation; (d) is a statistical diagram of the diameter of the inhibition zone of the AHA / THB@mSF / Ag hydrogel dressing prepared by the present invention against Pseudomonas aeruginosa and methicillin-resistant Staphylococcus aureus; (e) is the result diagram of the in vivo anti-Pseudomonas aeruginosa of the AHA / THB@mSF / Ag0 and AHA / THB@mSF / Ag2 hydrogel dressings prepared by the present invention under near-infrared irradiation.

[0040] Figure 11(a) is Tegaderm TMWound contraction rates of burn wounds in mice treated with film, AHA / THB@mSF / Ag0 hydrogel dressing, AHA / THB@mSF / Ag2 hydrogel dressing, and AHA / THB@mSF / Ag2 hydrogel dressing + near-infrared light irradiation group on the 5th, 10th, and 18th days; Figure 11(b) is the histological observation of wound regeneration tissue; Figure 11(c) is the statistical graph of wound gaps on the 18th day.

[0041] Fig.12 Schematic diagram of the preparation method of AHA / THB@mSF / Ag hydrogel dressing and its application in burn wounds. DETAILED DESCRIPTION

[0042] The present invention is further described in detail below in conjunction with the accompanying drawings:

[0043] In the description of the present invention, it should be noted that the terms "center", "upper", "lower", "left", "right", "vertical", "horizontal", "inside", "outside" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention; the terms "first", "second", and "third" are only used for descriptive purposes, and cannot be understood as indicating or implying relative importance; in addition, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection or a detachable connection; it can be directly connected or indirectly connected through an intermediate medium, and it can be the internal communication of two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0044] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments:

[0045] One of the embodiments of the present invention discloses a method for preparing a hydrogel dressing with photothermal antibacterial and silver ion antibacterial properties, which specifically comprises the following steps:

[0046] (1) 2.3.4-trihydroxybenzaldehyde oxidized self-polymerized coated silk microfibers (THB@mSF) were prepared. The preparation process was as follows: using scissors to cut silk cocoons, adding the silk cocoon fragments into a sodium carbonate solution, and boiling the sodium carbonate solution in a reactor for 30 minutes to obtain silk fibroin; using a strong alkaline solution to shear the degummed silk fibroin to obtain silk fibroin microfibers; using 2.3.4-trihydroxybenzaldehyde oxidized self-polymerized coated silk microfibers (THB@mSF), the self-polymerized coated silk is a coating formed by THB self-polymerization; more specifically, the following steps were included:

[0047] (1A) preparing a sodium carbonate solution with a mass concentration of 0.5%, cutting silk cocoons into pieces with scissors, adding the silk cocoon pieces into the sodium carbonate solution, and boiling the silk cocoon pieces in the 0.5% sodium carbonate solution for 30 minutes to obtain silk fibroin; washing the silk fibroin with deionized water, and drying it in a vacuum drying oven;

[0048] (1B) The silk fibroin was sheared with 17.5M sodium hydroxide particles, washed with water, and centrifuged, and repeated 3 to 5 times; the specific shearing process was as follows: 3.5 grams of sodium hydroxide particles (NaOH) (to obtain a 17.5M solution) were added to 5 mL of distilled water. When about 70% of the sodium hydroxide particles were dissolved in an exothermic reaction, 0.35 grams of dry degummed silk fibers were added and stirred with a spatula for 60 seconds.

[0049] (1C) Silk microfibers and 2.3.4-trihydroxybenzaldehyde were mixed at a mass ratio of 1:1 and reacted in an alkaline solution with a pH of 11 at 60°C for 2 h, so that the silk microfibers were wrapped by 2.3.4-trihydroxybenzaldehyde to obtain a THB@mSF dispersion. The specific reaction of this step is: 2.3.4-trihydroxybenzaldehyde with a catechol structure is reduced in a weak alkaline environment, self-polymerized on the surface of the silk microfiber, and a coating is formed on the surface of 2.3.4-trihydroxybenzaldehyde.

[0050] The final THB@mSF dispersion is: 2.3.4-trihydroxybenzaldehyde is wrapped around the outside of the silk microfibers as a coating, the silk microfibers are dispersed in an alkaline solution, and THB@mSF can still exist in the dispersion in the form of a microfiber structure.

[0051] (2) Amino modification of hyaluronic acid using adipic acid dihydrazide (AHA);

[0052] Adipic acid dihydrazide is added to the hyaluronic acid solution, and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 1-hydroxybenzotriazole are further added to the above solution. The pH of the stirred solution is adjusted, and the reaction is continued for a certain period of time, and then the solution is dialyzed and freeze-dried to obtain adipic acid dihydrazide-modified hyaluronic acid (AHA). More specifically, the preparation steps of AHA include:

[0053] (2A) preparing a hyaluronic acid solution at a concentration of 10 mg / ml, stirring the solution evenly, adding a 30-fold molar excess of adipic acid dihydrazide to the hyaluronic acid solution, and continuing to stir the solution evenly for reaction;

[0054] (2B) adding 5 mmol 1-(3-dimethylpropyl)-3-ethylcarbodiimide hydrochloride and 5 mmol 1-hydroxybenzotriazole dissolved in a DMSO / H2O (1:1) mixed solution to the above solution, and monitoring the pH in real time to stabilize the pH value at 6.8 for 4 hours to keep the reaction efficiency of the catalyst at all times, and then after reacting for 12 hours, dialyzing with a dialysis bag with a molecular weight cutoff of 10,000 for 5-7 days;

[0055] (2C) adding sodium chloride to the dialyzed aqueous solution to form a 5% (w / v) solution, and precipitating with excess ethanol;

[0056] (2D) The precipitate was dissolved with deionized water, and the aqueous solution was dialyzed with deionized water using a dialysis bag with a molecular weight cutoff of 10,000 for 5-7 days and then freeze-dried to obtain adipic acid dihydrazide-modified hyaluronic acid (AHA).

[0057] (3) dissolving AHA in water to obtain an AHA solution with a concentration of 20 mg / ml;

[0058] (4) Dissolve silver nitrate in water to obtain a silver nitrate solution; after the THB@mSF dispersion and the AHA solution are evenly mixed, the silver nitrate solution is added to obtain a hydrogel dressing with photothermal antibacterial and silver ion antibacterial properties; in this step, the THB@mSF dispersion and the AHA solution are first mixed to allow the precursor solution to initially act on the Schiff base to produce a stable cross-linked network, and then silver nitrate is added to form silver nanoparticles (AgNPs) in situ in the hydrogel network to prevent the sudden release effect of the nanoparticles. The steps for preparing the hydrogel dressing with photothermal antibacterial and silver ion antibacterial properties include:

[0059] (4A) The concentration of THB@mSF dispersion was 24 mg / mL; amino-modified hyaluronic acid was dissolved in deionized water at a concentration of 20 mg / ml, and silver nitrate was dissolved in deionized water at concentrations of 1.32, 2.64, and 3.96 mg / ml, respectively.

[0060] (4B) 100 μl-300 μl of THB@mSF dispersion was added to 600 μl of AHA solution. Subsequently, AgNO3 solution was added to the prepolymer at a molar ratio of THB / AgNO3 of 0.5:1 to induce gelation, and the remaining volume was supplemented with deionized water to ensure a total volume of 1000 μl, and the polymer network was cross-linked to form.

[0061] The final hydrogel network is formed through the following reactions: (1) After THB@mSF is oxidized, the phenolic hydroxyl groups of THB react with the aldehyde groups of THB and the amino groups of AHA; (2) After THB@mSF is oxidized, the phenolic hydroxyl groups undergo oxidative coupling with the phenolic hydroxyl groups in THB; (3) AgNPs are complexed with AHA and THB@mSF, and AgNPs are also dispersed in the hydrogel network.

[0062] A hydrogel dressing with photothermal antibacterial and silver ion antibacterial properties is prepared by the above preparation method. Because the hydrogel dressing contains silver ions, it has antibacterial properties under non-photothermal conditions. At the same time, the hydrogel dressing also has photothermal antibacterial properties under near-infrared laser (808nm) irradiation and can be used as a photothermal agent.

[0063] Furthermore, a hydrogel dressing with photothermal antibacterial and silver ion antibacterial properties can be used as a wound dressing in the areas of antibacterial properties and full-thickness wound repair of burn wounds.

[0064] Furthermore, the hydrogel dressing with photothermal antibacterial and silver ion antibacterial properties was able to inhibit methicillin-resistant Staphylococcus aureus and Pseudomonas aeruginosa.

[0065] The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it.

[0066] Example 1

[0067] (1) Self-polymerized coated silk microfibers (THB@mSF) oxidized by 2.3.4-trihydroxybenzaldehyde

[0068] Preparation of SF: 2.5 g of silkworm cocoons were boiled in 1 L of 0.02 M Na2CO3 aqueous solution for 30 min to obtain SF. SF was washed with distilled water and air-dried at room temperature.

[0069] Preparation of mSF: Sodium hydroxide pellets (NaOH, 17.5 M) were added to 5 mL of distilled water. When about 70% of the NaOH pellets were dissolved by an exothermic reaction, 0.35 g of dried degummed SF was added and the reaction was stirred with a spatula for 60 seconds. To stop the hydrolysis, 45 mL of water was added to the reaction mixture and centrifuged at 3,500 rpm for 5 minutes. The supernatant was discarded and the mSF was resuspended in 50 mL of water, stirred and centrifuged. This step was repeated five to eight times to remove excess residual alkali. The pH of the solution was measured and adjusted to 7.0 using hydrochloric acid. The neutralized mSF solution was centrifuged again at 3,500 rpm for 5 minutes and resuspended in water (repeated 3 to 5 times). Finally, the mSF was suspended in PBS and lyophilized to produce mSF powder.

[0070] Preparation of THB@mSF: 24 mg mSF and 24 mg THB were dissolved in 1 ml water and reacted at 60°C for 10 minutes. A strong base solution was added to the reaction system and reacted at 60°C for 2 hours to obtain a THB@mSF dispersion for later use.

[0071] Example 2

[0072] (2) using adipic acid dihydrazide to modify hyaluronic acid by amino group;

[0073] Preparation of AHA: 1 g of hyaluronic acid was dissolved in deionized water to make a 10 mg / ml solution. A 30-fold molar excess of adipic acid dihydrazide was added to the solution. 0.78 g of 1-(3-dimethylpropyl)-3-ethylcarbodiimide hydrochloride and 0.77 g of 1-hydroxybenzotriazole were dissolved in DMSO / H2O (1:1 v / v, 5 ml each) and added to the reaction mixture. The pH of the solution was adjusted to 6.8 by adding HCl and maintaining for at least 4 hours, and the reaction was allowed to proceed overnight. Subsequently, the pH was adjusted to 6.8 and the reaction solution was dialyzed thoroughly (MWCO10,000) for 5-7 days. Then, NaCl was added to produce a 5% (w / v) solution, and the amino hyaluronic acid reaction solution was precipitated in ethanol. The precipitate was redissolved in water and dialyzed again to remove salts. The purified product was freeze-dried and stored at 4°C.

[0074] Example 3

[0075] The concentration of THB@mSF dispersion was 24 mg / ml; AHA was dissolved in deionized water at a concentration of 20 mg / ml, and silver nitrate was dissolved in deionized water at a concentration of 1.32 mg / ml. To prepare the AHA / THB@mSF / Ag composite hydrogel, first, a 100 μl volume of THB@mSF dispersion was added to 600 μl of AHA solution. Subsequently, AgNO3 solution was added to the prepolymer at a molar ratio of 0.5:1 according to THB / AgNO3 to induce gelation. The remaining volume was supplemented with deionized water to ensure a total volume of 1000 μl. The resulting composite hydrogel was denoted as AHA / THB@mSF / Ag1.

[0076] Example 4

[0077] The concentration of THB@mSF dispersion was 24 mg / ml; AHA was dissolved in deionized water at a concentration of 20 mg / ml, and silver nitrate was dissolved in deionized water at a concentration of 2.64 mg / ml. To prepare the AHA / THB@mSF / Ag composite hydrogel, first, a 200 μl volume of THB@mSF dispersion was added to 600 μl of AHA solution. Subsequently, AgNO3 solution was added to the prepolymer at a molar ratio of 0.5:1 according to THB / AgNO3 to induce gelation. The remaining volume was supplemented with deionized water to ensure a total volume of 1000 μl. The resulting composite hydrogel was denoted as AHA / THB@mSF / Ag2.

[0078] Example 5

[0079] The concentration of THB@mSF dispersion was 24 mg / ml; AHA was dissolved in deionized water at a concentration of 20 mg / ml, and silver nitrate was dissolved in deionized water at a concentration of 3.96 mg / ml. To prepare the AHA / THB@mSF / Ag composite hydrogel, first, a 300 μl volume of THB@mSF dispersion was added to 600 μl of AHA solution. Subsequently, AgNO3 solution was added to the prepolymer at a molar ratio of THB / AgNO3 of 0.5:1 to induce gelation. The resulting composite hydrogel was denoted as AHA / THB@mSF / Ag3.

[0080] Example 6

[0081] The concentration of THB@mSF dispersion was 24 mg / ml; AHA was dissolved in deionized water at a concentration of 20 mg / ml. To prepare the AHA / THB@mSF / Ag composite hydrogel, first, 200 μl of THB@mSF dispersion was added to 600 μl of AHA solution. The remaining volume was supplemented with deionized water to ensure a total volume of 1000 μl. The resulting composite hydrogel was denoted as AHA / THB@mSF / Ag0.

[0082] The composition of the hydrogel dressing of the present invention is as follows:

[0083] Table 1 The amount of each raw material added in the preparation of various hydrogel dressings

[0084]

[0085] The structural formula of THB used in the present invention is as follows:

[0086]

[0087] The structural formula of adipic acid dihydrazide used in the present invention is as follows:

[0088]

[0089] The structural formula of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride used in the present invention is:

[0090]

[0091] The structural formula of 1-hydroxybenzotriazole used in the present invention is:

[0092]

[0093] FIG. 1( a ) is a scanning electron microscope image of mSF prepared in Example 1 of the present invention, and FIG. 1( b ) is a scanning electron microscope image of THB@mSF. The comparison shows that the THB coating was successfully prepared.

[0094] X-ray photoelectron spectroscopy was used to determine the chemical composition of the surface layer of mSF and THB@mSF. The high-resolution C1s spectra of the samples are shown in Figure 2. Figure 2(b) and 2(c) As shown. The chemical shift of carbon in the original mSF was integrated into four binding energy peaks using Gaussian curve peak fitting. Considering the chemical structure of silk fibroin, the first peak in 2(c) is attributed to CC, the second peak is attributed to CO, the third peak is attributed to C=N, and the fourth peak is attributed to -COO. Except for the CC bond position, the remaining sub-peaks have changed. All these results show that THB was successfully coated on the surface of mSF as a coating.

[0095] Through photothermal testing, compared with pure mSF, it was found that THB@mSF has better photothermal performance (Figure 3(a)) and stable cyclic photothermal performance (Figure 3(b)). After three cycles, the temperature can still reach the initial value, which confirms that THB@mSF has relatively stable photothermal performance.

[0096] Figure 4(a) is a scanning electron micrograph of four hydrogels AHA / THB@mSF / Ag0, AHA / THB@mSF / Ag1, AHA / THB@mSF / Ag2, and AHA / THB@mSF / Ag3 prepared by the preparation method of the present invention. It can be seen that the hydrogel has a porous structure. Figures 4(b) and 4(c) are energy spectra of AHA / THB@mSF / Ag0 and AHA / THB@mSFM / Ag2 hydrogel dressings. Silver ions are evenly distributed in the hydrogel network, indicating successful cross-linking of silver ions in AHA / THB@mSF / Ag2 hydrogel dressings.

[0097] Figure 5(a) is a strain scan of the AHA / THB@mSF / Ag2 hydrogel dressing prepared by the present invention. When the strain reaches 123%, the hydrogel network collapses. Figure 5(b) is an alternating strain scan. The rheological behavior of the AHA / THB@mSF / Ag2 hydrogel dressing was switched from 1% to 500% under alternating strain for three cycles. When a low strain (γ=1%) is applied, G'>G"; when a high strain (γ=500%) is applied, the value of G' decreases and is lower than G", indicating that the hydrogel is broken and the internal network collapses. After applying a low strain (γ=1%), the values ​​of G' and G" can be restored to their original initial values. After repeating this three times, the G' and G" of the hydrogel can still be restored to their initial values.

[0098] Figure 6 The figure shows the adhesion strength of the hydrogel dressing to pig skin. When not doped with AgNO3, the adhesion strength of the hydrogel increased from 0.57 kPa to 1.18 kPa, and the strength was more than doubled. This is mainly due to the fact that the interaction between the catechol group and the amino group of the tissue increased with the increase of THB@mSF content. After adding the AgNO3 solution, the adhesion strength of the hydrogel increased from the original 3.08 kPa to 8.27 kPa, and increased with the increase of AgNO3 concentration. Compared with the hydrogel without AgNO3, the adhesion strength of the hydrogel group with added AgNO3 increased by 5.5 times, 6.7 times and 7.0 times, respectively.

[0099] Figure 7(a) is a swelling diagram of the AHA / THB@mSF / Ag hydrogel dressing prepared by the present invention. The test results of the hydrogel swelling behavior show that in the AHA hydrogel, as the content of silver nanoparticles in the hydrogel increases, the swelling rate of the hydrogel gradually increases; Figure 7(b) is a DPPH free radical scavenging rate diagram of the hydrogel dressing, and each component hydrogel has good antioxidant capacity.

[0100] FIG8 is a photothermal image of the AHA / THB@mSF / Ag hydrogel dressing prepared by the present invention. FIG8 is a photothermal image of the AHA / THB@mSF / Ag hydrogel dressing prepared by the present invention. 2 Temperature change curves of hydrogel dressings under different photothermal intensities. For AHA hydrogel, the temperature did not increase significantly after irradiation. The temperature of AHA / THB@mSF / Ag0 hydrogel increased by about 18.9°C after 10 minutes of near-infrared light irradiation. By increasing the relative mass of THB@mSF, the maximum achievable temperature was significantly increased to 31.4°C; Figure (b) is an infrared thermal image of the hydrogel dressing under 808nm irradiation.

[0101] Figure 9(a) is a graph showing the results of the cell activity test of mouse fibroblasts (L929) using the contact method with different concentrations of the AHA / THB@mSF / Ag hydrogel dressings prepared by the present invention. Only the cell viability of AHA / THB@mSF / Ag1 and AHA / THB@mSF / Ag2 is comparable to that of the TCP group, reaching more than 90%. However, only a small amount of live cells exist in the AHA / THB@mSF / Ag0 group and the AHA / THB@mSF / Ag3 group. Figure 9(b) is a live / dead staining image of L929 cells after contact with the AHA / THB@mSF / Ag hydrogel dressing prepared by the present invention for 24 hours. Only the cell morphology of the AHA / THB@mSF / Ag1 and AHA / THB@mSF / Ag2 hydrogel groups is consistent with TCP, which is spindle-shaped, and the number of live cells is comparable to that of the TCP group. There are almost no live cells in the other groups, indicating that the AHA / THB@mSF / Ag1 and AHA / THB@mSF / Ag2 hydrogel groups have good cell compatibility.

[0102] Figure 10 is an antibacterial graph of the AHA / THB@mSF / Ag hydrogel dressing prepared by the present invention. Among them, (a) is the antibacterial result graph of the AHA / THB@mSF / Ag hydrogel dressing prepared by the present invention after contacting Pseudomonas aeruginosa and methicillin-resistant Staphylococcus aureus. The bacterial killing rates of the PBS group on Pseudomonas aeruginosa and methicillin-resistant Staphylococcus aureus were both 0%. The bacterial killing rates of the AHA / THB@mSF / Ag0 hydrogel group on Pseudomonas aeruginosa and methicillin-resistant Staphylococcus aureus were 20% and 30%, respectively. The inhibition rates of AHA / THB@mSF / Ag1, AHA / THB@mSF / Ag2 and AHA / THB@mSF / Ag3 hydrogel groups against Pseudomonas aeruginosa and methicillin-resistant Staphylococcus aureus were all 100%; (b) is a graph showing the antibacterial results of the AHA / THB@mSF / Ag2 hydrogel dressing prepared in the present invention against Pseudomonas aeruginosa under near-infrared laser irradiation. In the graph, the number of bacteria in the PBS group did not show any change under NIR irradiation at different times. For the AHA / THB@mSF / Ag2 hydrogel dressing, the sterilization rate reached 41% after irradiation for 1 minute; the bacterial sterilization rate was 98% after irradiation for 3 minutes; when the irradiation time was extended to 5 minutes and 10 minutes, all the bacteria were killed; (c) is the antibacterial result diagram of the AHA / THB@mSF / Ag2 hydrogel dressing prepared by the present invention against methicillin-resistant Staphylococcus aureus under near-infrared laser irradiation. In the figure, the number of bacteria in the PBS group did not show any change under NIR irradiation at different times. For the AHA / THB@mSF / Ag2 hydrogel dressing, after irradiation for 1 minute, the sterilization rate reached 98%; when the irradiation time was extended to 3 minutes, 5 minutes and 10 minutes, all the bacteria were killed; (d) is a statistical diagram of the diameter of the inhibition zone of the AHA / THB@mSF / Ag hydrogel dressing prepared by the present invention against Pseudomonas aeruginosa and methicillin-resistant Staphylococcus aureus. The blank circular hole was used as the control group. It was found that the circle diameter of the control group had no diffusion effect, and methicillin-resistant Staphylococcus aureus and Pseudomonas aeruginosa only retained the original diameter of 8mm. The inhibition zone produced by the AHA / THB@mSF / Ag1 hydrogel group was smaller, and the quantitative statistics of the inhibition zone diameters were 10mm and 10mm, respectively. The AHA / THB@mSF / Ag2 group produced clearer and larger inhibition zones for both methicillin-resistant Staphylococcus aureus and Pseudomonas aeruginosa, with the inhibition zone diameters of 13mm and 18mm, respectively. The inhibition zone produced by the AHA / THB@mSF / Ag3 group was larger than that of the AHA / THB@mSF / Ag2 group.According to the statistical results, the inhibition zones are 14 mm and 19 mm respectively; Figure (e) is the result of the AHA / THB@mSF / Ag0 and AHA / THB@mSF / Ag2 hydrogel dressings prepared by the present invention against Pseudomonas aeruginosa in vivo under near-infrared irradiation. The number of AHA / THB@mSF / Ag0 hydrogels was slightly reduced, but the antibacterial effect was not obvious. Quantitative statistics showed that nearly 80% of the bacteria survived. Compared with the AHA / THB@mSF / Ag0 hydrogel group, nearly half (46%) of the hydrogels in the AHA / THB@mSF / Ag0 hydrogel group irradiated with near-infrared light were killed. AHA / THB@mSF / Ag2 had only fewer bacterial colonies, and 90% of the bacteria were killed. The antibacterial effect of the AHA / THB@mSF / Ag0 hydrogel group irradiated with near-infrared light was better than that of the AHA / THB@mSF / Ag2 group, with a sterilization rate of 95%.

[0103] Figure 11(a) is Tegaderm TM Film, AHA / THB@mSF / Ag0 hydrogel dressing, AHA / THB@mSF / Ag2 hydrogel dressing, AHA / THB@mSF / Ag2 hydrogel dressing + near-infrared light irradiation for the wound contraction rate of mouse burn wounds on the 5th, 10th and 18th days. After 5 days of treatment, the wound contraction rate was significantly higher than that of Tegaderm TM Compared with the film group, the wound closure degree of the AHA / THB@mSF / Ag0 hydrogel dressing, AHA / THB@mSF / Ag2 hydrogel dressing, and AHA / THB@mSF / Ag2 hydrogel dressing + near-infrared light irradiation group was significantly higher, and on the 18th day of wound repair, the wound of the AHA / THB@mSF / Ag2 hydrogel dressing + near-infrared light irradiation group was completely healed. TM Comparison of thin films showed that the AHA / THB@mSF / Ag2 hydrogel dressing + near-infrared light irradiation group had a better effect in promoting burn wound healing; comparison between the various hydrogel groups showed that both silver ion antibacterial and photothermal antibacterial in the AHA / THB@mSF / Ag2 hydrogel dressing + near-infrared light irradiation group had a positive effect on burn wound healing.

[0104] Figure 11(b) shows the histological observation of the regenerated tissue of the burn wound. On the 10th day of wound repair, both the AHA / THB@mSF / Ag2 hydrogel dressing and the AHA / THB@mSF / Ag2 hydrogel dressing + near-infrared light irradiation group grew epidermis, but the epidermis of the AHA / THB@mSF / Ag2 hydrogel dressing + near-infrared light irradiation group was more regular. Figure (c) shows the statistical diagram of the wound gap on the 18th day. TMThe wound gaps of the film group, AHA / THB@mSF / Ag0 hydrogel dressing, AHA / THB@mSF / Ag2 hydrogel dressing and AHA / THB@mSF / Ag2 hydrogel dressing + near-infrared light irradiation group were 1616μm, 1167μm, 865μm and 0μm, respectively.

[0105] Fig.12 Schematic diagram of the preparation method of AHA / THB@mSF / Ag hydrogel dressing and its application in burn wounds.

[0106] The experimental results show that the photothermal properties, rheological properties, self-healing properties, mechanical strength, swelling rate, tissue adhesion strength, DPPH free radical scavenging rate, etc. of the hydrogel dressing prepared by the present invention can be adjusted by changing the content of THB@mSF and silver nitrate. The experimental results verify that the hydrogel dressing with photothermal antibacterial synergistic with silver ion antibacterial can show sufficient superiority in antibacterial, burn wound full-thickness damage repair, etc. by conducting contact antibacterial, antibacterial zone, photothermal antibacterial, in vitro antibacterial experiments and mouse back burn wound full-thickness damage repair model experiments.

[0107] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a hydrogel dressing with synergistic antibacterial effects of light, heat and silver ions, characterized in that: The following steps are involved: After the THB@mSF dispersion and the AHA solution were mixed in a volume ratio of (100-300):600, a silver nitrate solution was added, and the silver ions in the silver nitrate solution became silver nanoparticles to obtain a hydrogel dressing; The preparation process of the THB@mSF dispersion is as follows: adding silkworm cocoon fragments into a sodium carbonate solution, boiling to obtain silk fibroin, shearing the silk fibroin with a strong alkaline solution to obtain silk fibroin fibers, mixing the silk fibroin fibers with 2,3,4-trihydroxybenzaldehyde, and reacting in an alkaline solution to obtain the THB@mSF dispersion; The preparation process of the AHA solution is as follows: adding adipic acid dihydrazide, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 1-hydroxybenzotriazole to a hyaluronic acid solution, stirring evenly and adjusting the pH value to obtain a mixed solution, dialyzing the mixed solution, adding ethanol to the dialyzed mixed solution to obtain a precipitate, dialyzing and freeze-drying the precipitate to obtain AHA, and dissolving AHA in water to obtain an AHA solution; The silver nitrate solution is a mixture of silver nitrate and water; The concentration of the silver nitrate solution is 1.32-3.96 mg / mL; the concentration of the THB@mSF dispersion is 24 mg / mL, and the concentration of the AHA solution is 20 mg / mL.

2. The method for preparing the photothermal and silver ion synergistic antibacterial hydrogel dressing according to claim 1, characterized in that: During the preparation of THB@mSF dispersion, the mass concentration of sodium carbonate solution was 0.50%; the boiled silk was washed and dried, and the silk was sheared by a strong alkaline solution; The process of shearing the silk fibroin is: shearing the silk fibroin with a 17.5 M sodium hydroxide solution, washing the sheared silk fibroin with water and performing a centrifugal treatment to obtain the sheared silk fibroin.

3. The method for preparing the photothermal and silver ion synergistic antibacterial hydrogel dressing according to claim 1, characterized in that: During the preparation of THB@mSF dispersion, silk fiber and 2,3,4-trihydroxybenzaldehyde were mixed in a molar ratio of 1:1, and reacted in an alkaline solution with a pH value of 11 at 60°C to obtain a THB@mSF dispersion.

4. The method for preparing the photothermal and silver ion synergistic antibacterial hydrogel dressing according to claim 1, characterized in that: During the preparation of the AHA solution, the concentration of the hyaluronic acid solution is 20 mg / mL, the molar ratio of adipic acid dihydrazide to hyaluronic acid is 30:1; the molar ratio of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to 1-hydroxybenzotriazole is 1:1; and the mixing ratio of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to hyaluronic acid is 5 mol:1g.

5. The method for preparing the photothermal and silver ion synergistic antibacterial hydrogel dressing according to claim 1, characterized in that: During the preparation of the AHA solution, the pH was adjusted to 6.8, and the reaction was carried out for 12 h after the pH was stabilized for 4 h.

6. A photothermal and silver ion synergistic antibacterial hydrogel dressing prepared by the preparation method according to any one of claims 1 to 5, characterized in that: The main structure is a hydrogel network, in which silver nanoparticles are dispersed; in the hydrogel network, the phenolic hydroxyl group of THB, the aldehyde group of THB and the amino group of AHA are connected, the phenolic hydroxyl group of THB is connected to the phenolic hydroxyl group in THB, the silver nanoparticles are connected to AHA, and the silver nanoparticles are connected to THB.

7. An application of the photothermal and silver ion synergistic antibacterial hydrogel dressing according to claim 6, characterized in that: The hydrogel dressing acts as a photothermal agent under 808 nm near-infrared laser irradiation.

8. The use of the photothermal and silver ion synergistic antibacterial hydrogel dressing according to claim 7, characterized in that: The hydrogel dressing is used to inhibit methicillin-resistant Staphylococcus aureus and Pseudomonas aeruginosa.

9. The use of the photothermal and silver ion synergistic antibacterial hydrogel dressing according to claim 7 or 8, characterized in that: The hydrogel dressing is used for repairing burns, wound surfaces and full-thickness wounds.

Citation Information

Patent Citations

  • Hyaluronic acid self-crosslinking hydrogel taking oxidized hydroxyethyl cellulose as crosslinking agent, and preparation method thereof

    CN107383397A

  • Silver ion polysaccharide polymer antibacterial dressing and preparation method and application thereof

    CN112451738A